Projection-type integral imaging system using a three-dimensional screen composed of a lens array and a retroreflector film - Kim, Young Min; Song, Byoungsub; Min, Sung-Wook (OPTICAL SOC AMER, 2017)
We propose an improved projection-type integral imaging system using a three-dimensional (3D) screen consisting of a lens array and a retroreflector film in this paper. The projection-type integral imaging system suffers from the disadvantage of low-visibility images because of the inherently small exit pupil size of the projector. In order to resolve this problem, we adopt a 3D screen to avoid the demerits of a diffuser screen, such as off-screen image blur and loss of parallax. To determine the appropriate configuration of the 3D screen in the system, a simulation based on a ray transfer matrix analysis method was performed. The results show that the 3D screen should be located near the central depth plane of the integral imaging system, which leads to the conclusion that only the real mode is available for the proposed system. Experiments to verify this configuration and the feasibility of the proposed system were conducted using a system constructed with a real mode integral imaging system including a convex mirror array, which can fundamentally eliminate the pseudoscopic problem. (C) 2017 Optical Society of America
Keywords: HOLOGRAPHIC OPTICAL-ELEMENT; MIRROR ARRAY; DISPLAY; DEPTH; PHOTOGRAPHY; RESOLUTION; FIELD